Study of Maximum Swimming Speed Tilapia (Oreochromis Niloticus) for Fisheries Management - Ridha Primeswari; Nofrizal '; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study was to determine the swimming speed of the free swimming intank and flume tank, an outdoor durability of tilapia (Oreochromis niloticus), and maximumswimming speed tilapia in flume tank. Therefore, to use experimental methods. Free swimmingspeed was 0,25 BL/sec, maximum swimming speed of fish occurs when the fish are given ashock to swim. Negative correlation between speed and endurance swimming R2 = 0,7295 showsa fish swimming endurance decreases at higher speeds. Sustained tilapia swimming speed of<1,91 BL/sec. Prolonged swimming speed effect tired very high the body of the fish. Tilapia hasprolonged speed of 1,91 to 16,28 BL/sec. Maximum swimming speed tilapia is >16,28 BL/sec,while fish baung 10,5 BL/sec. Frequency flick of the tail of the fish in the aquarium has anegative correlation with R2 = 0,0161, whereas in the flume tank has a positive correlation withR2 = 0,4471. The amplitude flick of the tail of the fish in the aquarium and in the flume tank hasa negative correlation with the value R2 = 0,0004 and R2 = 0,903.Keywords: tilapia (Oreochromis niloticus), flume tank, swimming speed, free swimming speedand maximum swimming speed.